AGE-RELATED FEATURES OF THE CARDIOVASCULAR SYSTEM (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Aging has a profound impact on the cardiovascular system, leading to structural and functional changes that affect overall health and well-being. This article examines age-related characteristics of the cardiovascular system, including changes in cardiac structure, vascular function, and hemodynamic regulation. Understanding these changes is essential for optimizing preventive strategies to prevent age-related cardiovascular disease and promote healthy aging.